THE INFLUENCE OF THE AGE, SEX AND PERFORMANCE LEVEL OF HORSES ON THEIR SUCCESS IN THE SHOW JUMPING COMPETITION - Miroslav MARŠÁLEK; Markéta SEDLÁČKOVÁ; Markéta SECKÁ (Journal of Central European Agriculture, 2006)
The aim of this thesis is to clarify the effect of the horse age, the horse sex and the performance rating of the horse on the resulting course passing. Altogether it was judged 1 825 horses during 44 courses. It represents 20 457 passed fences. The cogency of detected differences was determinated by the F-test and the following t-test with the signifi cance levels P≤0,05(+) , P≤ 0,01(++) a P≤0,001(+++). From the results analysis emerged the following statistically confi rmative establishment and fi ndings: The stallions reach higher percentage of clear jumping than the mares and the geldings. The jump refuse is more frequent in mares (3,62 %). The best results in course passing reach horses between the ages of 12 – 13 years, the performance of older horses declines.The fence passing is not differs markedly after the performance level of the horse. Better results reached horses in the courses of “Z” level (1,24) and the „T“ level (1,36). It indicates that 100 cm high is not very diffi cult to pass over for young horses and through the courses of the „T“ level are the best horses.